2021
DOI: 10.1371/journal.pmed.1003808
|View full text |Cite
|
Sign up to set email alerts
|

The EmpaTeach intervention for reducing physical violence from teachers to students in Nyarugusu Refugee Camp: A cluster-randomised controlled trial

Abstract: Background School-based violence prevention interventions offer enormous potential to reduce children’s experience of violence perpetrated by teachers, but few have been rigorously evaluated globally and, to the best of our knowledge, none in humanitarian settings. We tested whether the EmpaTeach intervention could reduce physical violence from teachers to students in Nyarugusu Refugee Camp, Tanzania. Methods and findings We conducted a 2-arm cluster-randomised controlled trial with parallel assignment. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The evidence on the negative effects of adverse experiences in childhood is well established and exposure to violence, as well as to stressors related to displacement and the refugee experience, are known risk factors for developing mental health disorders [ 54 , 55 ]. To date only one intervention to prevent and reduce school violence in humanitarian settings has been rigorously tested [ 40 ] and while the evidence on effective school-based ways to support mental health and psychosocial wellbeing of refugee children is growing, there remain large evidence gaps [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The evidence on the negative effects of adverse experiences in childhood is well established and exposure to violence, as well as to stressors related to displacement and the refugee experience, are known risk factors for developing mental health disorders [ 54 , 55 ]. To date only one intervention to prevent and reduce school violence in humanitarian settings has been rigorously tested [ 40 ] and while the evidence on effective school-based ways to support mental health and psychosocial wellbeing of refugee children is growing, there remain large evidence gaps [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used data from the baseline survey of the Preventing Violence Against Children in Schools (PVACS) study which is a cluster randomized controlled trial assessing the effectiveness of the EmpaTeach intervention to change teacher practices and reduce use of violence in schools [ 40 ]. A cross-sectional survey was conducted between November and December 2019 with a representative sample of teachers and students in all 27 primary and secondary schools in the camp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary prevention programs in schools provide students with additional training and academic support in disadvantaged areas, so they can reduce violence and the socioeconomic consequences of adolescents’ school delay ( Romero et al, 2018 ). Fabbri et al (2021) demonstrated that teachers with low salary acted more aggressively ( Fabbri et al, 2021 ). Devries et al (2021) believed that economical condition, availability of facilities, a large number of students and supporting system for teaching affected teachers’ behaviors ( Devries et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%